Improving Fiber Optics Transmission Using Double Carrier Modulation / Differential Detection Technique (DCM/DiffD) - M.K, Abdullah; Abbas, Naseer; A.F, Abas (Malaysian Journal of Science, 2003)
DCM/DiffD is proposed here as a new transmission and detection technique which provides longer transmission distance than the conventional technique. This technique uses amplitude subtraction between original data bits and their inversion to provide a simple dynamic decision making scheme. The inverted data basically serve as the threshold in place of the conventional externally injected voltage. DCM/DiffD technique is shown here to double the eye opening and improves the performance significantly. BER of as good as 10Ã¢ÂÂ»Ã‚Â¹Ã¢ÂÂ´ at STM-16 rate over 150 km transmission distance with 0 dBm transmit power is demonstrated in this report. The new technique also shows a much slower degradation with distance than that of the conventional IM/DD systems.